THE EFFECT OF CONTROLLING SHAREHOLDERS AND CORPORATE GOVERNANCE ON AUDIT QUALITY - Annisa Anafiah, Vidyata Annisa; Diyanty, Vera; Wardhani, Ratna (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
This research aims to investigate the effect of controlling shareholders and the effectiveness of board of commissioners and audit committee on the audit quality measured by AQMS (Audit Quality Metric Score). This study uses companies listed in the Indonesian Stock Exchange as the sample. The results of this research provide evidence that alignment and entrenchment effect of the controlling shareholders have positive effect on audit quality. The alignment of interests between the controlling and non-controlling shareholders cause the company to appoint a high-quality auditor. The results also show that when companies face high entrenchment effect of the controlling shareholders, they still appoint a high-quality auditor to reduce the agency conflict and to maintain the company’s reputation. This research also shows that the effectiveness of board of commissioners and audit committee positively affect the audit quality.